2008
DOI: 10.1029/2007ja012994
|View full text |Cite
|
Sign up to set email alerts
|

A statistical look at plasmaspheric drainage plumes

Abstract: [1] The properties of plasmaspheric drainage plumes are examined using cold-plasma measurements in geosynchronous orbit. During high-speed stream-driven storms, 210 plume crossings are collected and statistically analyzed. Plumes that persist for 4 days are common, which was the duration of our search. Plumes weaken with age, becoming narrower in local time with plasma that becomes less dense. Cold-plasma flow velocities are sunward in the plumes, with flow speeds decreasing as the storms progress. Plumes tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
322
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(348 citation statements)
references
References 112 publications
(162 reference statements)
24
322
2
Order By: Relevance
“…The solar wind source is of the order of ∼ 10 27 ions s −1 and the high-latitude ionospheric source is of the order of ∼ 10 26 ions s −1 , varying by a factor of ∼ 3 as a function of the activity level and particularly dependent on the IMF orientation (Moore et al, 2005;Haaland et al, 2009;Li et al, 2012). The plasmaspheric plumes, which are a persistent feature during active periods, contribute during these periods by typically ∼ 2 × 10 26 ions s −1 to the magnetospheric populations (Borovsky and Denton, 2008). It appears thus that the plasmaspheric wind constitutes a substantial plasma source for the magnetosphere, outside the plasmasphere, which is comparable to the other sources and which operates continuously, even during prolonged periods of quiet geomagnetic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The solar wind source is of the order of ∼ 10 27 ions s −1 and the high-latitude ionospheric source is of the order of ∼ 10 26 ions s −1 , varying by a factor of ∼ 3 as a function of the activity level and particularly dependent on the IMF orientation (Moore et al, 2005;Haaland et al, 2009;Li et al, 2012). The plasmaspheric plumes, which are a persistent feature during active periods, contribute during these periods by typically ∼ 2 × 10 26 ions s −1 to the magnetospheric populations (Borovsky and Denton, 2008). It appears thus that the plasmaspheric wind constitutes a substantial plasma source for the magnetosphere, outside the plasmasphere, which is comparable to the other sources and which operates continuously, even during prolonged periods of quiet geomagnetic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…If the fluctuations reported here are measured where plumes are actually generated, this may be relevant to their suggestions. Another aspect is the turbulent nature of plumes, examined by Borovsky and Denton (2008). Although our study does not focus on this feature, further study on this topic would advance our understanding of the time evolution of plumes.…”
Section: Future Prospectsmentioning
confidence: 99%
“…McFadden et al (2008) reported density fluctuations inside plumes measured by THEMIS (Time History of Events and their Macroscopic Interactions during Substorms) satellites. Borovsky and Denton (2008) examined density fluctuations and their relation to turbulence using LANL geosynchronous data.…”
Section: Introductionmentioning
confidence: 99%
“…We discuss this further at the end of the paper. We will also argue that both our results and those of Bruno et al (2003) strongly favor the interpretation that the solar wind MHD scale cascade is active and not passive as sometimes suggested (Borovsky 2008). The present results also raise some interesting questions regarding the initial-boundary data for solar wind fluctuations.…”
Section: Introductionmentioning
confidence: 57%